ALOKASI ANGGARAN KEBIJAKAN MAKANAN BERGIZI GRATIS (MBG): TINJAUAN HUKUM EKONOMI SYARIAH DAN RELEVANSINYA DENGAN SDGS ZERO HUNGER - Desi Devrika Devra (Komunitas Manajemen Kompetitif, 2026)
The Free Nutritious Meal (MBG) program is President Prabowo Subianto's priority policy to address stunting. However, its universal tax-funded mechanism from the state budget raises fiscal justice concerns, as the financial burden is universally shared while direct benefits remain partial. This mixed-method socio-legal study aims to analyze MBG’s fiscal justice dimension through public policy, Maqashid Sharia, and SDGs Zero Hunger. The findings indicate that MBG aligns with Maqashid Sharia in protecting life, wealth, and public interest by stimulating local economies. Although a fiscal justice gap persists due to uneven distribution, it is offset by long-term national productivity gains. In conclusion, its sustainability relies on transparent governance and expanding distribution to remote areas to ensure inclusive distributive justice